Captured Glance : The Avant-Garde and Advertising in the Twenties (New York : Helen Serger, la boetie, inc., 1987)
Schwitters, Kurt ; van der Leck, Bart ; Stenberg brothers ; Dexel, Walter ; Klutsis, Gustav ; Chashnik, I.G. ; Höch, Hannah ; Bayer, H. ; Moholy-Nagy, L. ; etc.
Captured Glance : The Avant-Garde and Advertising in the Twenties, Helen Serger, la boetie, inc., New York, April 4 - May 29, 1987
boek